2015
DOI: 10.2174/0929866522666150622101223
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Peptides According to their Blood-Brain Barrier Influx

Abstract: An increasing number of studies demonstrate the ability of peptides to cross the blood-brain barrier (BBB), opening perspectives for a new class of therapeutics for central nervous system diseases. However, information on the BBB transport of peptides suffer from a wide variety in used methods and experimental set-up. Therefore, it is currently difficult, if not impossible, to classify peptides according to their BBB influx characteristics. To allow direct comparison of BBB influx results of peptides, we intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…The brain influx rate (K in ) and the distribution volume (V i ) obtained from fitting the model is shown in Table 1. As expected, the negative control, BSA, showed lower K in and V i values than the positive control, dermorphin, even though it is generally regarded to have relatively low influx [38]. For MCoTI-II, a K in value of 9.37 × 10 À5 μl/g/min was obtained, which is lower than that of BSA, indicating that it has no or very limited influx into the brain.…”
Section: Resultssupporting
confidence: 55%
“…The brain influx rate (K in ) and the distribution volume (V i ) obtained from fitting the model is shown in Table 1. As expected, the negative control, BSA, showed lower K in and V i values than the positive control, dermorphin, even though it is generally regarded to have relatively low influx [38]. For MCoTI-II, a K in value of 9.37 × 10 À5 μl/g/min was obtained, which is lower than that of BSA, indicating that it has no or very limited influx into the brain.…”
Section: Resultssupporting
confidence: 55%
“…For the first model using The BBB-influx classification system for peptides as proposed by Stalmans et al (2015b) indicated that BEA and ENNs are located in class 5, corresponding to a very high brain influx, which was also confirmed by comparing our obtained influx data of BEA/ENNs with those of other peptides (Van Dorpe et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…As negative and positive control, 125 I labelled BSA and dermorphin were used, respectively, to assure the overall validity of the experiment (Stalmans et al, 2015b). Furthermore, the influence of the ethanol-containing dose formulations on the BBB integrity was also investigated in a radioactive MTR influx study with 125 I radiolabelled BSA.…”
Section: Blood-to-brain Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…For EEG Signals Analysis, Li et al [62] proposed an innovative hybrid automated sleep stage scoring method called HyCLASSS with the basis of single channel EEG. For Molecule, to enable comparing blood-brain barrierinflux (BBB) results of peptides directly, Stalmans et al [63] proposed an innovative classification approach and unified response for BBB transport of peptides. For Brain-Computer-Interface, Schettini et al [64] proposed and evaluated a novel approach for the automated recalibration of the classifier's parameters.…”
Section: Plos Onementioning
confidence: 99%